Teaching the perception of educational, scientific and song texts of mathematical subject at the elementary level of teaching Russian as a foreign language - Vostryakova, Natalya A. (Yazyk i kul'tura, 2024)
The article analyzes the introductory-subject course of mathematics from the popular complex “Russian language for a future engineer”, created by a team of experienced teachers of the Moscow Automobile and Road Institute. This preparatory course is used at the preparatory faculties of many Russian universities and consists of eight lessons, the tasks of which are presented in two parts of the complex – in the book for the student and the teacher’s book. The lessons of the course are studied in Russian as foreign language classes, starting from the second or third week of study, but are based on the school mathematical program and test foreignersʼ knowledge of the main topics of arithmetic – types of numbers and operations with them. They form elementary skills in reading, pronunciation, writing Russian cardinal numbers (numbers) and mathematical terms and prepare students for classes with a mathematics teacher. Based on his own long-term experience of working with the “Russian language for a future engineer” complex, the author emphasizes the effectiveness of this introductory subject course and its accessibility for students from different countries in the first month of studying Russian as a foreign language. At the same time, its study often gives rise to problem situations in a foreign audience, which must be resolved in the educational process. They may be related to the following: – the studied vocabulary in the book for the student is not provided with stresses, which complicates its assimilation by students; – understanding the terms “natural numbers”, “rational numbers”, completing tasks to reduce fractions to a common denominator, reducing fractions can cause difficulties for foreigners; – the concept of irrational numbers, mathematical root, root extraction is absent in the course; – most of the terms from the course are poorly remembered by students, rarely improve their vocabulary and are used by them in speech; – Lessons 3–8 usually do not evoke an emotional reaction in students and interest in learning mathematics in Russian. In order to increase the efficiency of the introductory course in mathematics from the “Russian Language for a Future Engineer” complex, it is advisable to take into account the circumstances outlined and level them with the help of additional educational comments, methodological materials, and special forms of work. Therefore, in this study, the following goals were set: for foreigners of the elementary level of studying Russian as a Foreign Language, to create educational and scientific texts on arithmetic(maths), deepen and systematize this preparatory course, to find a thematically authentic song text that is accessible in the first months of studying the Russian language and allowing to stimulate studentsʼ interest in mathematics; based on educational, scientific and song texts, develop a practical lesson on Russian as a foreign language and in the process of experimental training to test its effectiveness. When performing the research, methods of linguistic and methodological analysis, pedagogical observation, the method of a teaching experiment and other scientific methods and techniques were used. As a result of the study, a practical lesson was created on the topic: “Numbers, their types and arithmetic operations”. It is based on four texts: three educational and scientific texts created by the author “Arithmetic and types of numbers”, “Arithmetic operations”, “How to reduce a fraction” and the authentic song text “Two times two is four” by composer V.Ya. SHainskij and the poet M.S. Plyatskovsky. These texts perform different tasks in the lesson. Educational and scientific texts generalize and supplement the introductory subject course of mathematics of the complex, taking into account the moments that are difficult for foreigners in its content. They demonstrate examples of the use of mathematical vocabulary by students as part of sentences and text, allow them to adequately comprehend and repeat it. Authentic song text complements the content of the preparatory course on the material of the artistic style of speech. It is presented first in the form of audio, then video, which allows you to train the receptive mechanisms of foreigners in many ways and contributes to its understanding. By means of art, with the help of the combined effect of music, lyrics and visual film images, the song text emphasizes the importance of arithmetic knowledge in human life, evokes an emotional reaction in students and increases their interest in learning activities in Russian. All four texts in the lesson are equipped with a system of tasks that ensures their adequate perception and assimilation by foreigners of the elementary level of education. Acquaintance with them develops the mathematical competence of students, their secondary communication skills in all types of speech activity, as well as the ability to perceive a work of musical art in Russian. Unfamiliar vocabulary in the lesson is provided with a translation into English, which makes it possible to use it in the audience of native and secondary native speakers of English, which make up the majority of the contingent of preparatory faculties of modern Russian universities. Depending on the level of language training and the characteristics of the formation of the group, the lesson can be held immediately after studying the introductory subject course of mathematics from the complex “Russian language for a future engineer” or within one to two months after that. Despite the fact that the lesson is aimed at students of a technical profile, it can be used both in economic and medical groups, the curriculum of which also involves the study of a preparatory arithmetic course in Russian.